Min-Maximalism A study of the musical limitations and possibilities imposed by the creative process of composing for the SNES leading to a composition made with similar tools and principles - Øien,Gabriel Carstensen (2024)
In this written study, I have researched video game music from the 90’s and early 2000’s to see what I can learn from the process of composing music for video games, as well as how the hardware and software capabilities of the game consoles shaped the music. First it presents my own background and relation to the subject, next it establishes what functionally separates video game music from conventional music. Finally, it analyses two compositions from the game EarthBound before presenting and discussing the result of my research which is my own composition “Attack of The Bell Demon”. The main conclusions are that the composers were influenced by the creative process associated with video game music, as well as their backgrounds in sound design and intimate knowledge of synthesis and sampling.
Keywords: [Composition; Jazz; Video Game Music; Chiptune; SNES; Nintendo; EarthBound; Mother 2]